2015
DOI: 10.4103/2231-4040.154529
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-inflammatory, mutagenic and antimutagenic activities of ethanolic extract of Clerodendrum paniculatum root

Abstract: Clerodendrum paniculatum L. (Family Verbenaceae) has been used as an antipyretic and anti-inflammatory drug in traditional Thai medicine. This present study investigated the in vitro anti-inflammatory, mutagenic and antimutagenic activities of the ethanolic extract of C. paniculatum (CPE) dried root collected from Sa Kaeo Province of Thailand. Murine macrophage J774A.1 cells were stimulated by lipopolysaccharide (LPS) to evaluate nitric oxide (NO), tumor necrosis factor-α (TNF-α) and prostaglandin E2 (PGE2) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Percentage of inhibition was calculated based on the following Equation (1) where T is the number of revertants per plate in the presence of both the mutagen and FDD, and M is the number of revertants per plate in the presence of the mutagen alone. The percentage of inhibition was classified as follows: higher than 60%, strong; 60% to 41%, moderate; 40% to 21%, weak; and < 20%, negligible [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Percentage of inhibition was calculated based on the following Equation (1) where T is the number of revertants per plate in the presence of both the mutagen and FDD, and M is the number of revertants per plate in the presence of the mutagen alone. The percentage of inhibition was classified as follows: higher than 60%, strong; 60% to 41%, moderate; 40% to 21%, weak; and < 20%, negligible [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The percent of inhibition between 0–20%, 21–40%, 41–60%, and higher than 60% indicate negligible, weak, moderate, and strong anti-mutagenicity, respectively [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, AF-2 (0.1 µg/mL) was used in the absence of the S9 mixture in the test of both strains. The percentage inhibition (decrease revertant colony number) was calculated as in the following equation: The percent of inhibition between 0-20%, 21-40%, 41-60%, and higher than 60% indicate negligible, weak, moderate, and strong anti-mutagenicity, respectively [27].…”
Section: In Vitro Mutagenicity and Anti-mutagenicity Assessment Using...mentioning
confidence: 99%
“…Recent studies have indicated that the anti-inflammatory effects of Cynanchum paniculatum and its derivatives are related to the modulation of the immune system, especially regulating the macrophages activation [ 10 , 27 , 36 ]. Antofine and its analogues could inhibit the LPS-induced nitric oxide (NO) production in RAW 264.7 macrophage cells [ 36 , 37 ].…”
Section: Immunomodulatory Effect Of Cynanchum Paniculatumentioning
confidence: 99%
“…Researchers identified many secondary metabolites from Cynanchum paniculatum , including phenol derivatives, polysaccharides, glycosides, and alkaloids [ 4 7 ]. Pharmacological research shows that the chemical composition or extract of Cynanchum paniculatum has analgesic, sedative, anti-inflammatory, antibacterial, antiallergic, and anticancer effects [ 3 , 8 – 10 ]. Cynanchum paniculatum is widely used for treating gastroenterological, oncological, dermatological, and orthopedics diseases in CM practices.…”
Section: Introductionmentioning
confidence: 99%